In vitro assessment of cytochrome P450 2C9 inhibition: tolbutamide as probe substrate and HepaRG cells as human hepatic model - Gomes, Ana Inês Pacheco Vaz (2016)
Pharmacokinetics information, especially regarding the drug metabolic profile, is a requirement during the preclinical and clinical development. In vitro methodologies represent more and more useful tools to predict drug safety and toxicity. The cytochrome P450 (CYP450) enzymes are the main responsible for the variability in pharmacokinetics and drug response, being the cytochrome (CYP) 2C9 isoform representative of about 20% of total hepatic CYP450 content, and one of the most important drug-metabolizing isoenzymes. Consequently, the prediction of drug interactions mediated by the inhibition of the CYP2C9 isoenzyme may be of great relevance in the development of new drugs. Due to the fact that HepaRG, a new human cell line derived from a hepatocellular carcinoma, is being considered a promising model to evaluate the in vitro metabolism of drugs, it was herein used for the development of an in vitro methodology for the investigation of CYP2C9 inhibition-based metabolic drug-drug interactions. The high-performance liquid chromatography–diode-array detection (HPLC-DAD) assay developed, enabled the simultaneously quantification of tolbutamide (TOL) and its metabolite 4-hydroxytolbutamide (4-OH-TOL), in HepaRG cell culture medium samples, supporting the subsequent in vitro studies. Chromatographic separation of the analytes (4-OH-TOL and TOL) and the internal standard (IS), carbamazepine (CBZ), was achieved in less than 20 minutes by a gradient elution on a reversed-phase LiChroCART® Purospher Star column (C18, 55 mm × 4 mm; 3 µm particle size), at 35 °C, using a mobile phase composed of phosphate buffer (10 mM) with 0.1% triethylamine (pH 3)/acetonitrile pumped at 0.6 mL/min. The analytes and IS were detected at 230 nm. The method proved to be selective, accurate, precise and linear (r2 = 0.9901) over the concentration ranges of 0.25-200 µM for TOL and 0.25-20 µM for 4-OH-TOL. Furthermore, the absolute recovery of the analytes ranged from 73.2 to 84.8% and their stability was demonstrated in the studied conditions. HepaRG cells were used in the metabolic inhibition studies, in which the reference drugs used as CYP2C9 inhibitors (amiodarone, fluoxetine, ketoconazole, omeprazole and ticlopidine) or flavonoids [baicalein, (-)-epigallocatechin gallate, kaempferol and quercetin] were pre-incubated for 30 minutes, and then TOL (200 µM), a known CYP2C9 probe drug, was co-incubated with the CYP2C9 inhibitors or flavonoids (24 hours). The suitability of the in vitro technique and the experimental analytical procedures developed and validated in the evaluation of potential metabolic inhibition interactions involving the CYP2C9 was demonstrated by the inhibitory effect observed with almost all the concentrations of CYP2C9 inhibitors. Moreover, all the flavonoids also demonstrated to inhibit the CYP2C9 isoenzyme, with exception of baicalein at 50 µM, validating the methodology applicability. This work demonstrated the usefulness of the in vitro assay developed and validated in the HepaRG cell line as a useful in vitro approach to foresee metabolic interactions involving the CYP2C9 isoenzyme inhibition.